Clinical Outcomes of RTOG 9310 Protocol for Primary Central Nervous System Lymphoma: Single-Center Experience with 87 Patients - Jinuk Kim; Tae Gyu Kim; Hyoun Wook Lee; Seok Hyun Kim; Ji Eun Park; Moonok Lee; Young Zoon Kim (Current Oncology, 2021)
The Radiation Therapy Oncology Group (RTOG) 9310 protocol clinical trial established high-dose methotrexate (HDMTX) as the standard for primary central nervous system lymphoma (PCNSL). We aimed to investigate the RTOG 9310 protocol’s PCNSL outcomes by examining progression-free survival (PFS) and overall survival (OS) rates and determining the influential factors. Between 2007 and 2020, 87 patients were histopathologically diagnosed with PCNSL and treated with the RTOG 9310 protocol. All received HDMTX 2.5 g/m2 and vincristine 1.4 mg/m2/day for 1 day during weeks 1, 3, 5, 7, and 9, and procarbazine 100 mg/m2/day for 1 day during weeks 1, 5, and 9. Dexamethasone was administered on a standard tapering schedule from the first week to the sixth week. Whole brain radiotherapy (WBRT), consisting of 45 Gy for patients with less than a complete response to the chemotherapy or 36 Gy for complete responders, was started 1 week after the last dose of chemotherapy was administered. Within three weeks of the completion of WBRT, patients received two courses of cytarabine, which were separated by 3–4 weeks. Clinical, radiological, and histopathological characteristics were retrospectively reviewed. All patients completed five HDMTX cycles and a mean follow-up of 60.2 (range, 6–150) months. Twenty-eight (32.2%) patients experienced recurrence during follow-up. The mean time to recurrence was 21.8 months, while the mean PFS was 104.3 (95% confidence interval (CI), 90.6–118.0) months. Eleven (12.6%) patients died; the mean OS was 132.1 (95% CI, 122.2–141.9) months. The 3- and 5-year survival rates were 92.0% and 87.4%, respectively. One patient experienced acute renal failure, while the remainder tolerated any cytotoxic side effects. On multivariate analysis, the Eastern Cooperative Oncology Group performance score ≤ 2; the International Extranodal Lymphoma Study Group low-risk status; XBP-1, p53, and c-Myc negativity; homogenous enhancement; gross total resection, independently correlated with long PFS and OS. The RTOG 9310 protocol is effective for PCNSL and features good outcomes.